Carta al director del diario El día del arabista Antonio Almagro Cárdenas sobre la inauguración de la Iglesia de la Inmaculada de Tánger en 1881 - LOPEZ GARCIA, Bernabé (Revista de Estudios Internacionales Mediterráneos, 2015)
“Letter to the Director of the Newspaper El día from the Arabist Antonio Almagro Cárdenas regarding the Inauguration of the Church of the Inmaculada in Tangier in 1881”